Integrasi Anggaran Responsif Gender Dalam Anggaran Pendapatan Belanja Daerah - Nur Khaerah; Dyah Mutiarin (Universitas Muhammadiyah Yogyakarta, 2016)
The gap between gender equality policies and gender responsive budgeting is still ....in Indonesia’spublic finance (Sopanah,2004). This brings negative impacts to the society, in particular women,because the proportion of public expenditure for women’s interest is still very low (less than 5% of totalbudget). Such condition requires the commitment of the Government to realize gender equality bymainstreaming gender perspective on various mechanism, policies and budgeting. This research aimsto analyze the integration of gender responsive budgeting in regional expenditure at Department ofHealth in Makassar Municipality in 2014. This research used qualitative methods of which the primarydata were collected through in-depth interview and documentation. The result indicated that theallocation of gender specific budgeting was 4% with 26 posts and allocation of gender equalitybudgeting was 3% with 3 posts. Meanwhile general gender mainstreaming budgeting was unavailableor 0% of total direct expenditure at the Department of Health. There were several obstacles inimplementing gender responsive budgeting at the Department including the obstacles on policies,structural and cultural. Therefore, this research suggest to the national and provincial governments toactively do socialization and campaign on the implementation of gender responsive budgeting withinplanning, budgeting, implementation, monitoring and evaluation. It is also necessary to providetrainings for Regents/Mayors and Head of all Departments on this matter.